30 years brings changes to the arthropod community of Kibale National Park, Uganda. (7th February 2023) - Opito, Emmanuel A.; Alanko, Timo; Kalbitzer, Urs; Nummelin, Matti; Omeja, Patrick; Valtonen, Anu; Chapman, Colin A.
Abstract: World‐wide declines in arthropod abundance and diversity are a major concern, particularly given their importance in ecosystem functioning. Yet, data documenting long‐term trends are rare from the tropics, particularly the Afrotropics. Here we evaluate changes in the arthropod communities in Kibale National Park, Uganda across almost four decades. Systematic sweep‐net sampling was conducted in two forested sections of the park that had been logged and in one old‐growth forest area over 12 consecutive months in 1983/1984 and 2020/2021. This data was augmented with intermittent samples taken in 1986 and 1995. Arthropod abundance declined in all areas, but only significantly so in the moderately logged forestry compartment (41%). Permutational multivariate analysis of variance indicated that community compositions of arthropods differed between the censuses. Understanding the drivers of changes in the arthropod communities is difficult as the system is complex and dynamic. We document an increase in temperature, but no change in rainfall, increases in 11 mammal species, including a marked increase in elephant numbers, and changes in forest structure. We also report on changes in the landscape outside of the park, which includes the human population increasing by a factor of four and agricultural intensification that now includes the use of pesticides. We document that many components of the ecosystem we studied changed simultaneously, which signals that for effective conservation planning, more long‐term multi‐disciplinary efforts are needed. Abstract : Sweep‐net sampling conducted in 1983/1984 and 2020/2021 document declines in arthropods by up to 41% and snails by up to 98%. We document potential drivers of this change, including an increase in temperature, increases in 11 mammal species, including a marked increase in elephant numbers, changes in forest structure, and marked increase in the human population outside the park that corresponded with agricultural intensification that now includes the use of pesticides